Youth movements in the Egyptian transformation: strategies and repertoires of political participation. Issue 1 (2nd January 2016) - Abdalla, Nadine
Abstract: The accumulated research on youth movements in general, and on Egyptian ones in particular, analyses the characteristics of the youths who triggered the Arab Spring as well as the particular forms of activism and structures they adopted. Academic work focused on youth activism in Egypt, however, thus far lacks research on how the youth movements modified their strategies according to the political context and the repercussions this had on the transformation process. Hence, through the analysis of the strategies pursued by four youth movements during the course of the Egyptian transformation, this article will show that on one hand, the choice of a certain strategy could be successful in one political context but could fail to yield influence in another. On the other hand, it will show that the choice of a certain strategy can enable the movements to induce political change in the short term, but it can be liable to become ineffective in the longer term and vice versa.